Designing area of circle learning trajectory based on “what-if” questions to support students’ higher-order thinking skills - Payadnya, I Putu Ade Andre; Prahmana, Rully Charitas Indra; Lo, Jane-Jane; Noviyanti, Putu Ledyari; Atmaja, I Made Dharma (Universitas Sriwijaya in collaboration with Indonesian Mathematical Society (IndoMS), 2023)
The study material on circle areas is contextually oriented and aids students in comprehending their surrounding environment. Higher-order thinking skills are imperative for the success of circular learning, as they help students grasp concepts holistically and solve concept problems.